Observations supporting hypothetical commensalism and competition between two Campylobacter jejuni strains colonizing the broiler chicken gut - Chagneau, Sophie; Gaucher, Marie-Lou; Thériault, William P.; Fravalo, Philippe; Thibodeau, Alexandre (Frontiers in Microbiology, 2023)
Campylobacter jejuni is the most prevalent bacterial foodborne infections in humans. Given the wide genetic diversity of C. jejuni strains found in poultry production, a better understanding of the relationships between these strains within chickens could lead to better control of this pathogen on farms. In this study, 14-day old broiler chickens were inoculated with two C. jejuni strains (103 or 107 CFU of D2008b and 103 CFU of G2008b, alone or together) that were previously characterized in vitro and that showed an opposite potential to compete for gut colonization in broilers. Liver samples and ileal and cecal contents were collected and used to count total C. jejuni and to quantify the presence of each strain using a strain specific qPCR or PCR approach. Ileal tissue samples were also collected to analyze the relative expression level of tight junction proteins. While a 103 CFU inoculum of D2008b alone was not sufficient to induce intestinal colonization, this strain benefited from the G2008b colonization for its establishment in the gut and its extraintestinal spread. When the inoculum of D2008b was increased to 107 CFU – leading to its intestinal and hepatic colonization – a dominance of G2008b was measured in the gut and D2008b was found earlier in the liver for birds inoculated by both strains. In addition, a transcript level decrease of JAM2, CLDN5 and CLDN10 at 7 dpi and a transcript level increase of ZO1, JAM2, OCLN, CLDN10 were observed at 21 dpi for groups of birds having livers contaminated by C. jejuni. These discoveries suggest that C. jejuni would alter the intestinal barrier function probably to facilitate the hepatic dissemination. By in vitro co-culture assay, a growth arrest of D2008b was observed in the presence of G2008b after 48h of culture. Based on these results, commensalism and competition seem to occur between both C. jejuni strains, and the dynamics of C. jejuni intestinal colonization and liver spread in broilers appear to be strain dependent. Further in vivo experimentations should be conducted to elucidate the mechanisms of commensalism and competition between strains in order to develop adequate on-farm control strategies.